A Latent Class Analysis of Mental Health Beliefs Related to Military Sexual Trauma. Issue 2 (23rd September 2020) - Hahn, Christine K.; Turchik, Jessica; Kimerling, Rachel
Abstract: Military veterans with histories of military sexual trauma (MST) are at risk for several negative mental health outcomes and report perceived barriers to treatment engagement. To inform interventions to promote gender‐sensitive access to MST‐related care, we conducted an exploratory, multiple‐group latent class analysis of negative beliefs about MST‐related care. Participants were U.S. veterans ( N = 1, 185) who screened positive for MST within the last 2 months and reported a perceived need for MST‐related treatment. Associations between class membership, mental health screenings, logistical barriers, difficulty accessing care, and unmet need for MST‐related care were also examined. Results indicated a four‐class solution, with classes categorized as (a) low barrier, with few negative beliefs; (b) high barrier, with pervasive negative beliefs; (c) stigma‐related beliefs; and (d) negative perceptions of care (NPC). Men were significantly less likely than women to fall into the low barrier class (27.9% vs. 34.5%). Relative to participants in the low barrier class, individuals in all other classes reported more scheduling, p s < .001; transportation, p < .001 to p = .014; and work‐related barriers, p < .001 to p = .031. Participants in the NPC class reported the most difficulty with access, p < .001, and those in the NPC and high barrier classes were more likely to report unmet needs compared to other classes, ps < .001. Brief cognitive and behavioral interventions, delivered in primary care settings and via telehealth, tailored to address veterans' negative mental health beliefs may increase the utilization of mental health treatment related to MST. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐19‐0190.R2_Hahn_cantonese Traditional Chinese 與軍事性創傷有關的心理健康信念的潛等級分析 摘要 : 有過軍事性創傷史(MST)的退伍軍人有可能出現一些負面的心理健康結果, 並報告說他們認為存在治療障礙。為了告知干預措施, 促進對性別敏感的MST相關護理的獲取, 我們對MST相關護理的負面信念進行了探索性、多組潛在類分析。參與者為美國退伍軍人(N = 1, 185), 他們在過去2個月內對MST篩查呈陽性, 並報告認為需要進行MST相關治療。組別成員、心理健康篩查、後勤障礙、難以獲得護理和未滿足的MST相關護理需求之間的關聯也被調查。結果表明有四類解決方案, 其中級別分為:(a)低障礙, 有少數負面信念;(b)高障礙, 有普遍的負面信念;(c)與污名相關的信念;(d)對護理的負面看法(NPC)。男性屬於低障礙級別的可能性明顯低於女性(27.9%對34.5%)。相對於低障礙等級的參與者, 所有其他等級的人報告了更多的日程安排, p < .001;運輸, p < .001至p = .014;和工作相關的障礙, p < .001至p = .031。在NPC班的參與者報告了在訪問方面的最大困難, p < .001, 與其他組別相比, NPC和高障礙組的參與者更有可能報告未滿足的需求, ps < .001。在初級保健機構和通過遠程保健提供的簡短的認知和行為干預, 為解決退伍軍人的消極心理健康信念而量身定做, 可能會增加與MST有關的心理健康治療的利用率。 Simplified Chinese 与军事性创伤有关的心理健康信念的潜等级分析 摘要 : 有过军事性创伤史(MST)的退伍军人有可能出现一些负面的心理健康结果, 并报告说他们认为存在治疗障碍。为了告知干预措施, 促进对性别敏感的MST相关护理的获取, 我们对MST相关护理的负面信念进行了探索性、多组潜在类分析。参与者为美国退伍军人(N = 1, 185), 他们在过去2个月内对MST筛查呈阳性, 并报告认为需要进行MST相关治疗。组别成员、心理健康筛查、后勤障碍、难以获得护理和未满足的MST相关护理需求之间的关联也被调查。结果表明有四类解决方案, 其中级别分为:(a)低障碍, 有少数负面信念;(b)高障碍, 有普遍的负面信念;(c)与污名相关的信念;(d)对护理的负面看法(NPC)。男性属于低障碍级别的可能性明显低于女性(27.9%对34.5%)。相对于低障碍等级的参与者, 所有其他等级的人报告了更多的日程安排, p < .001;运输, p < .001至p = .014;和工作相关的障碍, p < .001至p = .031。在NPC班的参与者报告了在访问方面的最大困难, p < .001, 与其他组别相比, NPC和高障碍组的参与者更有可能报告未满足的需求, ps < .001。在初级保健机构和通过远程保健提供的简短的认知和行为干预, 为解决退伍军人的消极心理健康信念而量身定做, 可能会增加与MST有关的心理健康治疗的利用率。